Respostas
respondido por:
1
A equação do 2° Grau que admite -2 e 7 como raízes é equivalente a
RAIZES
x' = - 2
x" = 7
FÓRMULA da equação do 2º grau
(x - x')(x - x") = 0
(x -(-2))(x - 7) = 0
(x + 2)(x - 7) = 0
x² - 7x + 2x - 14 = 0
x² - 5x - 14 = 0 ( equação do 2º grau)
RAIZES
x' = - 2
x" = 7
FÓRMULA da equação do 2º grau
(x - x')(x - x") = 0
(x -(-2))(x - 7) = 0
(x + 2)(x - 7) = 0
x² - 7x + 2x - 14 = 0
x² - 5x - 14 = 0 ( equação do 2º grau)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás